Tinjauan Hukum Fiqih Muamalah Terhadap Sistem Komisi dalam Program Tiktok Affiliate - Najib Muhammad Iqbal; Muhammad Hamdi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to review the system commission in the TikTok Affiliate program from the perspective of muamalah fiqh law. The background of this research is based on the rapid development of digital businesses and social media, especially TikTok, which opens up new economic opportunities through affiliate programs. The research method used is qualitative with a descriptive-analytical approach, involving literature studies, in-depth interviews with physicists and digital business practitioners, and analysis of documents related to the TikTok Affiliate program. The results of the study show that the system in TikTok Affiliate reflects the principles of fairness and transparency regulated in fiqh muamalah. The program allows for a proportional commission sharing with the content creator's efforts, and provides a clear and transparent monitoring mechanism. However, to ensure compliance with sharia, it is important that the products promoted by creators are halal products and that all provisions regarding commissions are explained in detail to avoid the element of gharar (uncertainty). The conclusion of this study confirms that the commission system in TikTok Affiliate can be considered in accordance with the principles of fiqh muamalah, as long as all parties involved ensure that transactions are carried out fairly, honestly, and transparently, and the products promoted are in accordance with halal provisions.